(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of making this web-based information and entertainment portal application is to develop a portal that can be used by the public in obtaining entertainment and information about trends and lifestyle. In addition, this application is also made with the aim of developing information and entertainment portals that can facilitate content contributors so that they can share ideas and participate in the production of content available on this portal. The method used to develop this web-based information and entertainment portal application is the waterfall method using the Code Igniter framework. Evaluation of this application is carried out with two approaches namely questionnaire and comparison with similar applications. The end result of the development of this application is a web-based portal called Cacta Media that provides information and entertainment in the form of articles and videos